Analysis of Fiqh Learning Materials on Hajj and Umrah - Lubis, Nabilah; Rohman, Rohman; Hayati, Nelmi; Khairat, Annisaul (STIT Ahlussunnah Bukittinggi, 2025)
This study comprehensively examines the problems and determining factors of Fiqh Learning Problems in Hajj and Umrah Material among Students. This study was conducted at Al-Bi'tsatul Islamiyah Islamic Boarding School. The research method used was descriptive qualitative research with a case study approach. Data collection techniques in this study included observation, interviews, and documentation. The informants in this study were eighth-grade fiqh teachers, eighth-grade students, and the deputy head of the pesantren's Tsanawiyah. Data validity was ensured using source triangulation. The results of this study indicate that students have difficulty understanding the material on Hajj and Umrah due to the complexity of the rituals, limited learning media, and the dominance of lecture methods that are not interactive. The contributing factors include teachers' teaching experience that has not been balanced with innovation, limited time allocation, low student interest in learning, and a lack of facilities and infrastructure such as a miniature Kaaba. This study is expected to contribute to improving the quality of fiqh learning on hajj and umrah material in Islamic boarding schools.